LOW-TEMPERATURE PROPERTIES OF A SINGLE CRYSTAL OF MAGNETITE ORIENTED ALONG PRINCIPAL MAGNETIC AXES - Ozdemir O.; Dunlop D.J. (My University, 1999)
We have measured saturation induced and remanent magnetizations and induced magnetization as a function of field at low temperatures, between 300 K and 10 K, on an oriented 1.5-mm single crystal of magnetite. The induced magnetization curves along the cubic [001], [110], and [110] axes at 10 K have very different approaches to saturation. The crystal is easy to magnetize along [001] but difficult along [110] and [110], the hard directions of magnetization for monoclinic magnetite. The temperature dependence of saturation magnetization between the Verwey transition temperature, Tv = 119 K, and 10 K is also different along the three axes, indicating that below Tv the crystal has uniaxial symmetry. The room-temperature saturation remanence (SIRM) produced along [001] decreases continuously in the course of zero-field cooling, levelling out at the isotropic temperature, Ti = 130 K, where the first magnetocrystalline anisotropy constant becomes zero. At Ti, 86% of the initial SIRM was demagnetized. The domain wall pinning responsible for this soft remanence fraction must be magnetocrystalline controlled. The remaining 14% of the SIRM is temperature independent between Ti and Tv and must be magnetoelastically pinned. This surviving hard remanence is the core of the stable magnetic memory. The Verwey transition at 119 K, where the crystal structure changes from cubic to monoclinic, is marked by a discontinuous increase in remanence, indicating that the cubic [001] direction suddenly becomes an easy direction of magnetization. The formation of monoclinic twins may also affect the intensity of remanence below Tv. Reheating from 10 K retraces the cooling curve, with a decrease at Tv back to the original remanence level, which is maintained to 300 K. When SIRM is not along [001], the initial SIRM is larger but the reversible changes across the Verwey transition are much smaller. The SIRM produced at 20 K is an order of magnitude larger than the 300 K SIRM, but the only change during warming is a discontinuous and irreversible drop to zero at Tv.
Keywords: MAGNETITE; VERWEY TRANSITION; ORIENTED TRANSITION; SATURATION ISOTHERMAL REMANENCE; MONOCLINIC MAGNETITE